Vital root resection with radicular retrograde partial pulpotomy in furcation-involved maxillary molars in patients with periodontitis: technique description and case series considering clinical and economic aspects - Ciardo, Antonio; Rampf, Sarah; Kim, Ti-Sun (International endodontic journal, 2024)
Aim Conventional root resection in periodontally compromised furcation-involved maxillary molars requires preceding endodontic treatment and is therefore associated with loss of tooth vitality, higher invasiveness, treatment time and costs, and the risk of endodontic complications. Vital root resection (VRR) could overcome these disadvantages while establishing stable periodontal and endodontic conditions. This case series aimed to introduce the concept of one-stage VRR with radicular retrograde partial pulpotomy (VRRretro). Summary Seven vital maxillary molars with residual probing pocket depths (PPD) ≥ 6 mm and furcation ≥ class 2 of five patients with stage III/IV periodontitis were treated with VRRretro using mineral trioxide aggregate. Teeth with residual through-and-through furcations were additionally tunnelled. Follow-up up to 2.5 years postoperatively during supportive periodontal care included full periodontal status, percussion and thermal sensitivity testing. Periapical radiographs were obtained to rule out possible periradicular radiolucencies. All seven treated molars were in-situ at an average of 26.84 ± 5.37 months postoperatively and were clinically and radiographically inconspicuous independent of tooth position, the resected root, the need for tunnelling and the restorative status. The mean PPD on the seven treated molars was 4.02 ± 0.85 mm (6-10 mm) preoperatively and 2.62 ± 0.42 mm (3-4 mm) at the last follow-up. Clinical attachment level and bleeding on probing could also be decreased. The teeth showed no mobility over time and furcations class 2 were reduced to class 1 while the tunnelled furcations were accessible with interdental brushes. All molars reacted negatively to percussion and positively to thermal sensitivity testing. Key learning points In carefully selected cases considering patient- and tooth-related factors, VRRretro could be a promising treatment option to establish stable periodontal and endodontic conditions in furcation-involved maxillary molars while preserving tooth vitality.
Vorab veröffentlicht: 2. Februar 2024
Gesehen am 27.05.2024